HTML5 for mobile devices : status and challenges of mobile web development - Firtman, Maximiliano R. (O'Reilly Media, 2014)
"The market for mobile apps continues to evolve at a breakneck pace, as tablets join the parade of smartphones and feature phones. Join us for a hands-on webcast presented by Maximiliano Firtman author of Programming the Mobile Web, 2nd Edition, as he shows you how to build apps that access geolocation, accelerometer, multi touch screens and other features in these mobile devices. From this webcast you will learn: what do you need to know today to create mobile web experiences, current and future platforms, main challenges: performance, native vs web, battery usage, fragmentation, debugging, full screen webapps and hybrids, toolkit for successful HTML5 mobile apps."--Resource description page.